PENGARUH SOLUTION FOKUSED BRIEF COUNSELING (SFBC) UNTUK MENINGKATKAN SELF-ESTEEM SISWA KELUARGA BROKEN HOME DI MA ABDUL AZIZ BALUNG JEMBER - Siti Maftuhah; Nasruliyah Hikmatul Maghfiroh; Bhennita Sukmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Adolescents with low self-esteem tend to have negative self-perceptions, feelunworthy, and withdraw from their social environment. This condition is commonlyfound among students from broken home families, as they often believe that theirparents’ separation is their fault. Such beliefs can lead to prolonged sadness andemotional trauma. This study aims to evaluate the implementation of SolutionFocused Brief Counseling (SFBC) as an effort to improve the self-esteem ofstudents from broken home families at MA Abdul Aziz Balung, Jember. Self-esteemplays a crucial role in personal development and academic achievement, makingeffective intervention strategies essential in educational settings. The researchemployed a quasi-experimental method with a one-group pre-test and post-testdesign. The sample was selected using purposive sampling techniques. The experimental group received SFBC treatment. Data were collected using a self-esteem scale administered before and after the intervention. The results of the data analysis using a paired sample t-test indicated a significant increase in students’self-esteem after the intervention. This study provides an in-depth understanding ofthe extent to which SFBC can significantly contribute to enhancing the self-esteemof students from broken home backgrounds.